PENGARUH DISIPLIN, MOTIVASI KERJA DAN IKLIM KERJA TERHADAP KINERJA GURU SD SE-KECAMATAN LIMPUNG KABUPATEN BATANG - Siti Nur Asiyah, 12.5202.0101; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimstoanalyzethe influenceInfluenceof Dicipline, WorkMotivationandWork ClimateonTeacher Performanceatone District of Batang.Inthis studypopulation ofallprimary schoolteachersin the District ofBatangPNS, whereasthe sample usedwas 101persons asrespondentsto thecensustechnique. WitharespondentcriteriaPNSElementaryTeachersinthe DistrictEducation OfficeTrunkUnit.Measurementsusinga Likert scaleof 7 (seven) alternative answers. Testinstrumentsused arevalidity and reliability. While thetestmodel usedisthe coefficientof determinationandF test(goodnes of Fit). Testthis hypothesisusingregressionanalysis.Based onthe results ofthe studycan be summarized asfollows: (ii) Work Disciplinehas no impact onteacher performance,Â (i) Motivationhas positive and significant impactonteacher performance, and (iii) Work Climate has impact onteacher performance. Keywords:Â Discipline, Work Motivation, Work ClimateÂ andTeacherPerformance.